2015
DOI: 10.1542/peds.2014-3902
|View full text |Cite
|
Sign up to set email alerts
|

Snacks, Sweetened Beverages, Added Sugars, and Schools

Abstract: Concern over childhood obesity has generated a decade-long reformation of school nutrition policies. Food is available in school in 3 venues: federally sponsored school meal programs; items sold in competition to school meals, such as a la carte, vending machines, and school stores; and foods available in myriad informal settings, including packed meals and snacks, bake sales, fundraisers, sports booster sales, in-class parties, or other school celebrations. High-energy, low-nutrient beverages, in particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…The effective policy interventions targeted at the school level to reduce sugar consumption among school children were to have a school nutrition policy restricting SSBs. These findings are consistent with those reported in independent reviews on determinants of high sugar intake [49, 50]. Tobacco use is a well-established independent risk factor for NCDs and the most prevalent behavioral risk factor globally [51].…”
Section: Discussionsupporting
confidence: 91%
“…The effective policy interventions targeted at the school level to reduce sugar consumption among school children were to have a school nutrition policy restricting SSBs. These findings are consistent with those reported in independent reviews on determinants of high sugar intake [49, 50]. Tobacco use is a well-established independent risk factor for NCDs and the most prevalent behavioral risk factor globally [51].…”
Section: Discussionsupporting
confidence: 91%
“…The American Academy of Pediatrics Council on School Health and Committee on Nutrition advises using the minimal amount of added sugars necessary to promote the palatability, enjoyment, and consumption of nutrient-rich food items. 117 Thus, it is important to be judicious when including added sugars in children’s diets. SSBs, sweets, and sweetened grains are more likely to have a negative impact on diet quality, whereas sweetened dairy products and presweetened cereals may have a positive impact.…”
Section: Diet Quality and Added Sugars Intakementioning
confidence: 99%
“…127 The American Academy of Pediatrics concluded that data on NNSs are scarce in terms of the long-term benefits for weight management in children and adolescents or the consequences of long-term consumption. 117 Because of the lack of research in children, a recommendation either for or against the routine use of NNSs in the diets of children cannot be made at this time.…”
Section: Alternatives To Added Sugarsmentioning
confidence: 99%
“…Reducing fructose intake is also critical. The American Academy of Pediatrics provides clear guidelines to limit juice and sweetened beverage intake in children [97], and advocates limiting sales of sugar sweetened beverages (SSB) in schools [98]. Decreasing SSB has been shown to lead to weight loss in overweight children [99].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%